A cross sectional study on the relationship between nursing students' perception of clinical learning environment and the willingness to care for older adult patients - Mohammad Sistani Allahabadi; Hadi Khoshab; Farzad Esfandiary; Rouhollah Zaboli (Elsevier, 2021)
Background: Considering the increasing population of the older adults, caring for them is one of the challenges of health care systems and this requires highly skilled and expert nurses. Aim: The main objective of this study was to determine the relationship between nursing students' perception of clinical learning environment and their willingness to care for older adult patients in the future. Method: 334 nursing students participated in this cross-sectional study. The mean score of nursing students' perception of clinical learning environment and willingness in caring for the older adults and their relationship were evaluated by two questionnaires. Results: Results showed that there is a significant relationship between nursing students' perception of clinical learning environment and their willingness to care for older adult patients (P < 0.05). It was found that by age increasing, students' perception of clinical learning environment increases. Conclusion: Providing an effective educational environment can be useful in increasing students' perception of the learning environment and their attitudes toward care. This will increase students' willingness in caring for the older adult patients in the future.